Tempora mutantur...Regionalizm na przykładzie Regio-źródeł - cyfrowej bazy informacyjnej Książnicy Beskidzkiej w Bielsku-Białej = Regionalism on the example of Regio-sources - digital information base of Książnica Beskidzka in Bielsko-Biała (The Beskidy Library in Bielsko-Biała) - Kania, Beata (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article presents the practical and technical side of the Regio-resources information search database created by the Książnica Beskidzka in Bielsko-Biała. It is a cognitive, research, educational and cultural database. The article outlines the library's activities in the context of promoting regionalism, taking into account the area of socalled regional humanism. It explains the name of the Regio-resources and discusses the content of the database using examples of documents of sociallife collected in Książnica Beskidzka. It presents the principles of the database,its possibilities and purpose as well as the mechanism of searching for information and the validity of archiving ephemera prints. It also mentions other original databases created and developed by Książnica Beskidzka.
Keywords: archiwizacja; baza informacyjno-wyszukiwawcza; digitalizacja; Dokumenty życia społecznego; dostęp cyfrowy; humanizm regionalny; informacja; Książnica Beskidzka w Bielsku-Białej; software; Regio-źródła; regionalizm; technologie komputerowe; wycinki prasowe; zbiory biblioteczne; archiving; information-searchable database; digitalization; documents of social life; digital access; regional humanism; information; Książnica Beskidzka in Bielsko-Biała; regionalism; computer technology; press clippings; library collections